Heavy metals in marine mussels and mangrove snails: are the molluscs meals safe as poultry feeds too? - Yap, Chee Kong; Cheng, Wan Hee (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The concentrations of Cd, Cu, Pb and Zn were determined in the total soft tissues of snails Nerita lineata and mussels Perna viridis collected from Peninsular Malaysia. The metal levels were compared with established permissible limits or guidelines for human consumption to predict the possible toxicological consequences if those molluscs were to be used as poultry feeds. It is found that Cd, Cu and Zn were well below the guidelines while Pb levels in the snail populations exceeded the guidelines. However, it is assumed that the toxicological effects on the animals would be lesser due to two main reasons: i) poultry feeds are usually composed of a multiple composition and the molluscs feeds made up of < 50%; ii) the tolerance of molluscs to the toxins and metals could be better when compared to human. Thus, the molluscs meal can be potentially used as poultry feeds similarly to the fish meal.